Pengaruh Tingkat Kesehatan dan Pengangguran Terhadap Kemiskinan di Lampung Tahun 2021-2023 - Annisa Istikomah; Yuyun Kartika Sari; Vika Agustiyani; Misfi Laili Rohmi (Universitas 45 Surabaya, 2025)
The aim of this research is to determine the impact of health and unemployment on poverty in Lampung Province.This data reformulation is based on the publication of BPS Pode 2021-2023. This research uses panel data regression analysis and shows that disability (PG) has a significant positive effect on poverty (KM), but health status (TK) has no effect on poverty (KM). On the other hand, the unemployment rate and population influence poverty.